Growth outcome at 2 years using Fenton and Intergrowth-21st charts in infants less than 1500 g - Lara González García; Enrique García López; Belén Fernández Colomer; Laura Mantecón Fernández; Sonia Lareu Vidal; Marta Suárez Rodríguez; Rosa Arias Llorente; Gonzalo Solís Sánchez (Elsevier, 2022)
Introduction: There is no consensus on which neonatal chart is best to use in very low birth weight (VLBW) infants. The aim of the study was to compare the Fenton 2013 and Intergrowth-21st (IW-21) charts based on their predictive ability for somatometry at 2 years, as well as to analyze factors related to short stature at 2 years. Material and methods: Cohort of children with VLBW born between 2002 and 2017. Association between neonatal somatometry (z-score by Fenton and IW-21) and risk of short stature (<−2 DS), head circumference <−2 DS and malnutrition at 2 years (BMI < −2 DS) was analyzed (WHO charts). Results: 513 children with a mean gestational age of 30.05 ± 2.5 weeks were included. Birth and discharge weight z-score by Fenton and IW-21 were useful for predicting risk of short stature and malnutrition at 2 years (without differences in the AUC of the ROC curves). Weight z-score at discharge was also useful for predicting head circumference < −2 DS. At 2 years, prevalence of short stature, head circumference < −2 DS, and malnutrition was 17.2, 4.1, and 6.1%, respectively. Low weight for gestational age and length of stay were identified as independent risk factors for short stature at 2 years. Conclusions: Discharge weight z-score is useful for predicting risk of short stature, malnutrition and head circumference < −2 DS at 2 years in very low birth weight children, with no statistical difference between using Fenton or IW-21 charts. Resumen: Introducción: No existe consenso sobre qué gráfica neonatal es mejor utilizar en niños con muy bajo peso al nacer (MBPN). El objetivo del estudio fue comparar las gráficas de Fenton 2013 e Intergrowth-21st (IW-21) con base en su capacidad predictora de la somatometría a los dos años, así como analizar factores relacionados con talla baja a los dos años. Material y métodos: Cohorte de niños con MBPN nacidos entre 2002−2017. Se analizó la asociación entre la somatometría neonatal (z-score por Fenton e IW-21) y el riesgo de talla baja (<−2 desviación estándar [DS]), perímetro craneal < −2 DS y desnutrición a los 2 años (IMC < −2 DS) (gráficas OMS). Resultados: Se incluyeron 513 niños con una edad gestacional media de 30,05 ± 2,5 semanas. El z-score del peso al nacimiento y al alta por Fenton y por IW-21 resultaron útiles para predecir riesgo de talla baja y desnutrición a los dos años (sin diferencias en el AUC de las curvas ROC), siendo el z-score al alta útil además para predecir perímetro craneal < −2D. A los dos años, la prevalencia de talla baja, perímetro craneal < −2 DS, y desnutrición fue del 17,2, 4,1 y 6,1%, respectivamente. El bajo peso para la edad gestacional y la duración del ingreso neonatal se identificaron como factores de riesgo independientes para talla baja a los dos años. Conclusiones: El z-score peso al alta resulta útil para predecir riesgo de talla baja, desnutrición y perímetro craneal < −2 DS a los dos años en niños con muy bajo peso al nacer, sin diferencias estadísticas entre utilizar las gráficas de Fenton o IW-21.